Automatic government : the politics of indexation - Weaver, R. Kent (Washington, D.C. : Brookings Institution, 1988)
This book inquire the effect of the politics of indexation among policy makers. It further negates politicians the power to claim ad hoc grant for inflation adjustment.
Includes bibliographical references and index.
sju 21/01/2019
Loans
Keywords: Indexation (Economics); Indexation (Economics)